Forage Business at Breed Source Area of Ruminansia in Central Java Province - Muatip, Krismiwati; Widiyastuti, Titin; Hidayat, Nunung Noor; Purwaningsih, Hermin; Purwanto, Eko; Setya, Ghanis Ginanjar (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
Kebumen district is one of beef development centers in Central Java that requires numerous forage supplies (HPT). Farmers without personal foraging area have to buy forages almost on a daily basis. Forage business is an emerging and prospective business sector to improve farmersâ€™ welfare particularly the income. Government is therefore expected to support in terms of facility and infrastructure to maintain a sustainable business practice. Â The aim of this study was to investigate the necessity of forage business in cattle development center in Kebumen district, forage marketing channel, forage business revenue, profit margin, R/C ratio and government support in terms of infrastructure or policy related to forage business.